Women's Experience with Non‐Invasive Prenatal Testing and Emotional Well‐being and Satisfaction after Test‐Results. Issue 6 (30th June 2017) - van Schendel, Rachèl V.; Page‐Christiaens, G. C. M. Lieve; Beulen, Lean; Bilardo, Caterina M.; de Boer, Marjon A.; Coumans, Audrey B. C.; Faas, Brigitte H. W.; van Langen, Irene M.; Lichtenbelt, Klaske D.; van Maarle, Merel C.; Macville, Merryn V. E.; Oepkes, Dick; et al.
Abstract: Increasingly, high‐risk pregnant women opt for non‐invasive prenatal testing (NIPT) instead of invasive diagnostic testing. Since NIPT is less accurate than invasive testing, a normal NIPT result might leave women less reassured. A questionnaire study was performed among pregnant women with elevated risk for fetal aneuploidy based on first‐trimester combined test (risk ≥1:200) or medical history, who were offered NIPT in the nationwide Dutch TRIDENT study. Pre‐ and post‐test questionnaires ( n = 682) included measures on: experiences with NIPT procedure, feelings of reassurance, anxiety (State‐Trait Anxiety Inventory, STAI), child‐related anxiety (PRAQ‐R), and satisfaction. The majority (96.1%) were glad to have been offered NIPT. Most (68.5%) perceived the waiting time for NIPT results (mean: 15 days, range 5–32) as (much) too long. Most women with a normal NIPT result felt reassured (80.9%) or somewhat reassured (15.7%). Levels of anxiety and child‐related anxiety were significantly lower after receiving a normal NIPT result as compared to the moment of intake ( p < 0.001). Women with inadequate health literacy or a medical history (e.g. previous child with trisomy) experienced significantly higher post‐test‐result anxiety (Mean (M) STAI = 31.6 and 30.0, respectively) compared to those with adequate health literacy (M = 28.6) and no medical history (M = 28.6), indicating these women might benefit from extra information and/or guidance when communicating NIPT test‐results. Introducing NIPT as an alternative to invasive testing, led to an offer that satisfied and largely reassured high‐risk pregnant women.